Evaluation of three rapid oral fluid test devices on the screening of multiple drugs of abuse including ketamine. (May 2018) - Tang, Magdalene H.Y.; Ching, C.K.; Poon, Simon; Chan, Suzanne S.S.; Ng, W.Y.; Lam, M.; Wong, C.K.; Pao, Ronnie; Lau, Angus; Mak, Tony W.L.
Highlights: Rapid oral fluid test devices that include ketamine were assessed in drug abusers. Devices tested include DrugWipe ® 6S, Ora-Check ® and SalivaScreen ® . Tests include ketamine, opiates, methamphetamine, cannabis, cocaine and MDMA. Overall specificity and accuracy were satisfactory for all devices. SalivaScreen had the best overall sensitivity (and for ketamine, opiates, cocaine). Abstract: Rapid oral fluid testing (ROFT) devices have been extensively evaluated for their ability to detect common drugs of abuse; however, the performance of such devices on simultaneous screening for ketamine has been scarcely investigated. The present study evaluated three ROFT devices (DrugWipe ® 6S, Ora-Check ® and SalivaScreen ® ) on the detection of ketamine, opiates, methamphetamine, cannabis, cocaine and MDMA. A liquid chromatography tandem mass spectrometry (LCMS) assay was firstly established and validated for confirmation analysis of the six types of drugs and/or their metabolites. In the field test, the three ROFT devices were tested on subjects recruited from substance abuse clinics/rehabilitation centre. Oral fluid was also collected using Quantisal ® for confirmation analysis. A total of 549 samples were collected in the study. LCMS analysis on 491 samples revealed the following drugs: codeine (55%), morphine (49%), heroin (40%), methamphetamine (35%), THC (8%), ketamine (4%) and cocaine (2%). No MDMA-positive cases were observed. Results showed that the overall specificity and accuracy were satisfactory and met the DRUID standard of >80% for all 3 devices. Ora-Check ® had poor sensitivities (ketamine 36%, methamphetamine 63%, opiates 53%, cocaine 60%, THC 0%). DrugWipe ® 6S showed good sensitivities in the methamphetamine (83%) and opiates (93%) tests but performed relatively poorly for ketamine (41%), cocaine (43%) and THC (22%). SalivaScreen ® also demonstrated good sensitivities in the methamphetamine (83%) and opiates (100%) tests, and had the highest sensitivity for ketamine (76%) and cocaine (71%); however, it failed to detect any of the 28 THC-positive cases. The test completion rate (proportion of tests completed with quality control passed) were: 52% (Ora-Check ® ), 78% (SalivaScreen ® ) and 99% (DrugWipe ® 6S).